Relating food choice determinants with sociodemographic variables, health status and nutritional risk among community living older adults - Oliveira, L. (2022)
Background & aims: The aging process has physiological, psychological and social implications that interfere with food choice. This work aims to identify factors influencing food choice among community-living older adults and their relationship with social characteristics, health status and nutritional risk. Methods: Four hundred fifty-nine older adults (65 years old) living in Vila Nova de Gaia (Portugal) were interviewed by trained interviewers in a face-to-face situation. Results: Participants had a mean age of 73 years (SD = 6). The majority were women (64.0%), married (67.8%) and lived in their own home (80.2%). Several associations were found between factors that influence food choice and sex, problems with sense organs and pathologies/problems. Older adults at malnourished or at risk of malnutrition or with high cardiovascular risk attribute less importance to the food's content in additives, colorants and preservatives. We also found a positive association between weight status and the importance attributed to food availability and a negative association between weight status and the ease of chewing were found. Conclusion: Knowledge on the factors influencing food choice among older adults may provide essential information for more effective clinical and community interventions, and for the development of new products to facilitate healthy choices among community-living older adults. (c) 2022 European Society for Clinical Nutrition and Metabolism